The Role of Innovative Design in Improving the Competitiveness of Local Products in the Era of Globalization - Muajaroh, Alfi Nazihatul; Asiah, Siti; Inayati, Tatu E; Alpiah; Yuliawati, Teti; Srimarwati, Enong (Asian Journal of Multidisciplinary Studies, 2024)
In this era of globalization, local products are required to be able to compete in the international market, by examining the role of product innovation in increasing increasingly fierce corporate competition. In overcoming increasingly intense competition, companies need to adapt and develop products that can meet the changing needs of consumers. Innovative design is one of the main elements in increasing the competitiveness of local products, product innovation not only provides added value for consumers but also strengthens the company's position by differentiating it from competitors. Technology plays a role as the main driving factor in the innovation process, which allows companies to respond to market changes more quickly. However, the implementation of innovation faces various challenges, such as limited resources and a less supportive organizational culture. This article discusses the role of innovative design in increasing product-added value, building brand identity, and attracting the attention of global consumers. This article was created using the literature method. Companies can understand global market trends and consumer preferences more deeply, by designing more effective innovation strategies that are by market needs.